Analysis of the Arrangement of Dress for Women in Sharia Regional Regulations from a Human Rights Perspective - Hartina, Hartina; Abdussamad, Zamroni; Achir, Nuvazria (Estudiante Law Journal, 2025)
This study aims to analyze the regulation of dress for women in the Sharia Regional Regulation from the perspective of Human Rights by looking at the position of the Sharia Regional Regulation in the national legal system and laws and regulations and analyzing the Mukomuko Regional Regulation Number 5 of 2016, using normative juridical research methods with a Legislative, Historical, and Conceptual approach. This research needs to be carried out because of the large number of Sharia Regional Regulations that have emerged at the central government or local government scales that have the opportunity to trigger political, social and legal problems. Sharia Regional Regulations that enter the private space also harm Human Rights that have been guaranteed by the 1945 Constitution, such as in Mukomuko Regional Regulation Number 5 of 2016 which is found to violate Human Rights in principle. The formation of the Regional Regulation should be adjusted to national laws and regulations, namely paying attention to multicultural aspects and prioritizing the principles of Human Rights.